2005
DOI: 10.2220/biomedres.26.179
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of chlamydia trachomatis growth by human interferon-.ALPHA.: mechanisms and synergistic effect with interferon-.GAMMA. and tumor necrosis factor-.ALPHA.

Abstract: We have evaluated the effect of natural human interferon (IFN)-α on the growth of chlamydia trachomatis in human epithelial cells in vitro and revealed that IFN-α has reduced both growth and infectivity of C. trachomatis. The effect of IFN-α was reversed by the addition of exogenous L-tryptophan and iron to the culture medium, suggesting that antichlamydial effect of IFN-α was caused by depletion of intracellular tryptophan and iron, both of which are essential for chlamydial growth. When IFN-α was combined wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 24 publications
0
25
0
1
Order By: Relevance
“…[41][42][43] Thus, it is possible that interactions with the lipoplex, but not pDNA or CL alone, modulates and triggers some gene expressions, which are involved in programmed cell death or cytokine generation of innate or adaptive immune reactions. Consequently, cells treated with lipoplex die via apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…[41][42][43] Thus, it is possible that interactions with the lipoplex, but not pDNA or CL alone, modulates and triggers some gene expressions, which are involved in programmed cell death or cytokine generation of innate or adaptive immune reactions. Consequently, cells treated with lipoplex die via apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…No se han descrito estudios anteriores que permitan corroborar este resultado en la coinfección con estos patógenos, y una limitación importante de este estudio es el tamaño de la muestra. Nuestras observaciones concuerdan con estudios anteriores, llevados a cabo in vitro, que demostraron que el género Chlamydia induce la expresión de IFN-␥ 24 , causando la inhibición del crecimiento de C. trachomatis 25,26 ; otro estudio demostró aumento de expresión de IFN-␥ en pacientes con infección por VPH 13 . De las observaciones anteriores, se esperaría que la coinfección con VPH y con C. trachomatis tuviera un efecto aditivo sobre la expresión de IFN-␥, hipótesis confirmada con los resultados de este estudio.…”
Section: Resultsunclassified
“…In the case of chlamydiae, specifically, these persistent bacterial organisms remain viable. Adding to these concerns, in vitro data has demonstrated that persistent chlamydial levels are inversely proportional to TNF-alpha levels [Ishihara et al 2005;Takano et al 2005;Perry et al 1997]. In keeping with the relative lack of prospective clinical trial data with ReA in general, there are few prospective data evaluating anti-TNF therapy in ReA.…”
Section: Tumor Necrosis Factor-alpha Antagonistsmentioning
confidence: 99%